A ratiometric fluorescent formaldehyde probe for bioimaging applications. Issue 21 (18th February 2016) - He, Longwei; Yang, Xueling; Liu, Yong; Kong, Xiuqi; Lin, Weiying
Abstract : The first ratiometric fluorescent formaldehyde probe (RFFP ) has been engineered for bio-applications. Abstract : We have described a ratiometric fluorescent formaldehyde probe (RFFP) based on the 6-hydroxy naphthalene chromophore for the first time. The probe is suitable for ratiometric detection of formaldehyde both in the solution and living biological samples with two distinct emission bands.